Cytotoxicity, genotoxicity and gene expression changes elicited by exposure of human hepatic cells to Ginkgo biloba leaf extract. (November 2017) - Grollino, Maria Giuseppa; Raschellà, Giuseppe; Cordelli, Eugenia; Villani, Paola; Pieraccioli, Marco; Paximadas, Irene; Malandrino, Salvatore; Bonassi, Stefano; Pacchierotti, Francesca
Abstract: The use of Ginkgo biloba leaf extract as nutraceutical is becoming increasingly common. As a consequence, the definition of a reliable toxicological profile is a priority for its safe utilization. Recently, contrasting data have been reported on the carcinogenic potential of Ginkgo biloba extract in rodent liver. We measured viability, Reactive Oxygen Species (ROS), apoptosis, colony-forming efficiency, genotoxicity by comet assay, and gene expression changes associated with hepato-carcinogenicity in human cells of hepatic origin (HepG2 and THLE-2) treated with different concentrations (0.0005–1.2 mg/mL) of Ginkgoselect ® Plus. Our analyses highlighted a decrease of cell viability, not due to apoptosis, after treatment with high doses of the extract, which was likely due to ROS generation by a chemical reaction between extract polyphenols and some components of the culture medium. Comet assay did not detect genotoxic effect at any extract concentration. Finally, the array analysis detected a slight decrease in the expression of only one gene (IGFBP3) in Ginkgo-treated THLE-2 cells as opposed to changes in 28 genes in Aflatoxin B1 treated-cells. In conclusion, our results did not detect any significant genotoxic or biologically relevant cytotoxic effects and gross changes in gene expression using the Ginkgo extract in the hepatic cells tested. Highlights: Multiparameter analyses of Ginkgo biloba extract IDN5933 have been performed. The extract tested does not show genotoxic and carcinogenesis-inducing effects. For nutraceutical use, the composition of extracts should be strictly controlled.